Upgrading of bio-oil derived from biomass constituents over hierarchical unilamellar mesoporous MFI nanosheets - Lee, Hyung Won; Park, Sung Hoon; Jeon, Jong-Ki; Ryoo, Ryong; Kim, Wookdong; Suh, Dong Jin; Park, Young-Kwon (ELSEVIER SCIENCE BV, 2014)
Unilamellar mesoporous MFI nanosheets (UMNs) were, for the first time, applied to the catalytic pyrolysis of the constituents of lignocellulosic biomass: cellulose, hemicellulose and lignin. A representative mesoporous catalyst, Al-SBA-15, was also applied to the same process for the purpose of comparison. The catalysts were characterized by N2 adsorption-desorption, X-ray diffraction, temperature programmed desorption of ammonia, and transmission electron microscopy. The synthesized UMN catalyst was composed of a random assembly of zeolite nanosheets with a thickness of 2.5 nm. UMN was shown to have strong Bronsted acid sites, whereas Al-SBA-15 had weak acid sites. Catalytic pyrolysis experiments were carried out using Py-GC/MS. The product distribution was analyzed in order to evaluate catalytic activity. Acidity had a considerable influence on catalytic activity; UMN, with a higher acidity than Al-SBA-15, exhibited higher activities for cracking and deoxygenation, producing bio-oil with a lower oxygen content and with a better overall quality. Levoglucosan, which was the main product of the non-catalytic pyrolysis of cellulose, was converted to aromatics and furans on the acid sites of the catalysts. Ketones, alcohols and cyclo-compounds, the main products of the non-catalytic pyrolysis of xylan, were also converted to aromatics and furans by catalytic upgrading. The main products of the non-catalytic pyrolysis of lignin were phenolics, which were converted to aromatics and lighter phenolics (alkyl phenolics and methoxy phenolics) in the presence of catalysts. Increasing the catalyst dose improved the quality of the product oil even further. 2013 Elsevier By. All rights reserved.
Keywords: CATALYTIC FAST PYROLYSIS; ZEOLITE; AROMATICS; LIGNIN; HZSM-5; DEOXYGENATION; SELECTIVITY; COMPONENTS; CONVERSION; CHEMICALS